2014
DOI: 10.1063/1.4890595
|View full text |Cite
|
Sign up to set email alerts
|

Microsphere-chain waveguides: Focusing and transport properties

Abstract: It is shown that the focusing properties of polystyrene microsphere-chain waveguides (MCWs) formed by sufficiently large spheres (D ≥ 20λ, where D is the sphere diameter and λ is the wavelength of light) scale with the sphere diameter as predicted by geometrical optics. However, this scaling behavior does not hold for mesoscale MCWs with D ≤ 10λ resulting in a periodical focusing with gradually reducing beam waists and in extremely small propagation losses. The observed effects are related to properties of nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…It has been shown that by using microsphere-chain waveguides [24,25] focusing and resolutions can improved. Microsphere near-field nano-structures were observed and analyzed using picosecond pulses [26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that by using microsphere-chain waveguides [24,25] focusing and resolutions can improved. Microsphere near-field nano-structures were observed and analyzed using picosecond pulses [26].…”
Section: Introductionmentioning
confidence: 99%
“…The linear chains or arrays of resonant spheres can be used as coupled resonator optical waveguides, high-order spectral filters or sensor devices with the engineered photonic band structures and optical properties. [26][27][28][29][30][31][32][33][34][35] Developing this photonic technology based on using photonic atoms with uniquely identical resonant properties requires knowledge of the spectral shape of the optical propulsion peaks. To perform these studies, in this work we developed a method to precisely control the wavelength detuning between the laser emission line and WGMs in individual microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…Over the course of the past decade there has been significant development in regards to the fundamental properties and potential applications of photonic nanojets (PNJs) [1][2][3] and nanojet-induced modes (NIMs) [4][5][6][7][8][9][10], spanning the areas from biomedical optics to super-resolution imaging [11,12]. Dielectric microspheres provide strong concentration of electromagnetic power which can be used for ultraprecise surgery and for increasing the sensitivity of the photodetector devices [13].…”
Section: Introductionmentioning
confidence: 99%